2022
DOI: 10.3233/jcm-215590
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of regional agricultural production efficiency and empirical analysis of its influencing factors-based on DEA-CCR model and Tobit model

Abstract: The improvement of agricultural production efficiency and the transformation of production mode are the core of promoting agricultural modernization. Taking Chongqing as a sample case, this paper uses DEA-CCR Model, Malmquist Index and Tobit Model to calculate and analyze its agricultural production efficiency and its influencing factors, and accurately identifies the problems existing in its agricultural transformation and development. It has an important policy reference value for improving agricultural inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Literature review showed that APE is associated with various factors such as urbanization, the level of agricultural economic development and the industrial structure of agriculture [20][21][22]. Therefore, this paper established an explanatory variable and dependent variable based on panel regression model.…”
Section: Factors Influencing Agricultural Production Efficiency In Si...mentioning
confidence: 99%
See 1 more Smart Citation
“…Literature review showed that APE is associated with various factors such as urbanization, the level of agricultural economic development and the industrial structure of agriculture [20][21][22]. Therefore, this paper established an explanatory variable and dependent variable based on panel regression model.…”
Section: Factors Influencing Agricultural Production Efficiency In Si...mentioning
confidence: 99%
“…The spatiotemporal analysis of a single APE involves analysis of the changes in agricultural production. It is imperative to study the influencing factors of agricultural production based on the comprehensive results of APE to explore new strategies to improve APE and reduce ACE [20][21][22]. These findings can promote the improvement of APE, reduce waste resources and reduce the environmental pollution caused by agricultural production activities.…”
Section: Introductionmentioning
confidence: 99%
“…On the whole, the previous studies on the influencing factors of carbon emission efficiency are mostly conducted by generalized method of moments (GMM) estimation in academia, mainly including the urbanization rate (Zhou et al, 2022), innovation input (Gao et al, 2019), energy intensity (Lv et al, 2015), and environmental regulation (Long et al, 2013). Existing studies on higher education promoting the development of a low-carbon economy have been relatively mature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Jika diantara salah satu faktor produksi tidak ada, maka proses produksi tidak dapat berjalan dengan baik, terutama tiga faktor terdahulu seperti tanah, modal, dan tenaga kerja. Tanpa tenaga kerja apa yang dapat dilakukan, begitu pun juga dengan faktor lain seperti tanah, dan modal [15]. Dalam produksi usaha tani gambir, kegiatan pengolahan hasil adalah tahap yang penting, karena pada tahap inilah yang akan menentukan besar kecilnya perolehan hasil baik secara kualitas maupun kuantintas.…”
Section: Pendahuluanunclassified